Cardiomyocyte differentiation of pluripotent stem cells with SB203580 analogues correlates with Wnt pathway CK1 inhibition independent of p38 MAPK signaling - Laco Filip (Academic Press, 2016)
10.1016/j.yjmcc.2014.12.003